Traditional medicine and popular art in Peru - Ramírez León, Luis (2021)
This article is about showing the relationships of prominent objects of popular art with the practice of contemporary traditional medicine, as a product of the Andean cultural syncretic conception. These objects will be analyzed formally, iconographically and functionally within regional sociocultural contexts, interpreting them based on their links with traditional medicine and the Andean worldview that underpins them, and the deepening in this way in their significant dimension.